Research of the Voltage Stability of Distribution Network Connected Induction Machines - Chuong, Trinh Trong; Anh, Traong Viet; Tho, Tran Qoang; Deveikis, Tomas (Elektronika ir Elektrotechnika, 2015)
There are a lot of wind power plants based on double feed induction machine technology which are connected to electrical network. These usually don’t consider reactive power (even reactive power consumption), so they generally affect the entire network voltage stability and can cause instability in themselves and become no longer balanced by the torque. This paper presents a method to study the relationship between the active power and voltage at the point of common coupling (PCC) connected wind power plant to identify the voltage stability limit. It is a fundament to define a permitted operation region in complying with the voltage stability limit at the PCC connected wind power. DOI: http://dx.doi.org/10.5755/j01.eee.21.1.9804